NUGGET KALAKAI (STENOCHLAENA PALUTRIS) UNTUK PERBAIKAN GIZI PADA BALITA UNDERWEIGHT DI WILAYAH KERJA UPTD PUSKESMAS BENTOT KABUPATEN BARITO TIMUR - Kamula, Ari Natal; Fitri Yuliana; Fadhiyah Noor Anisa (LPPM Universitas Sari Mulia, 2023)
Background: Nutritional status is an expression of the balance of nutrients with the body's needs. Imbalance between nutrients and body needs will cause underweight in toddlers. Based on Riskesdas 2021, stunting toddlers in Central Kalimantan are 27.67%. Improving nutrition in underweight toddlers can be done with innovations in the form of kalakai nuggets (Stenochlaena Palutris). Objective: Analyzing the effect of kalakai nuggets as a nutritional improvement in underweight toddlers in the working area of the Bentot Health Center. Methods: This type of research usesquasi experimentalwith pretest and posttest control one group design. The sampling technique in this study used purposive sampling Results: The majority of underweight toddlers are male by 65% with ages 1-2 years by 56%. Toddlers who are underweight before giving Kalakai nuggets have an average of 8.56. Underweight toddlers after administration of kalakai nuggets averaged 8.72. Based on the data obtained, a normality test was carried out with the results of the Asymp value. Sig (2-tailed) is 0.002<0.05. Wilcoxon test results with a significance value of 0.000 <0.05(p < 0.05). Conclusion: The research results show significant difference between giving Nugget Kalakai to underweight toddlers. Giving kalakai nuggets is effective for gaining weight in underweight toddlers in the working area of the Bentot Health Center UPTD. Keywords: Nugget Kalakai, Underweight, Toddler